Pengaruh Kualitas Pelayanan dan Keragaman Produk Terhadap Kepuasan Konsumen pada Jaya Mart Kabupaten Pelalawan - Salwa Nabilah; Endang Sutrisna (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
Currently, one of the growing business sectors is the retail industry. The retail industry has undergone a significant transformation in recent decades, moving from traditional retail to more complex and diverse modern retail. This study aims to determine the effect of service quality, product diversity on customer satisfaction at Jaya Mart Pelalawan Regency. This research uses quantitative methods. The sampling technique is non-probability sampling using incidental/accidental sampling with a sample size of 99 respondents. The data obtained was processed using SPSS software version 25. The results of this study are: (1) service quality has a significant effect on customer satisfaction, (2) product diversity has a significant effect on customer satisfaction, (3) service quality and product diversity have a significant effect on customer satisfaction.